Cantos religiosos de senegaleses murides : escrita, leitura, poética vocal e performance - Rossa, Juliana (My University, 2018)
The world religion scene reveals itself as a complex and singular entangle, due to its expression and behavioral practices. There are diverse ways of religious belonging and practices, including on traditional monotheistic religions such as Islam. That is the case of Mouridism, a Sufi brotherhood originated in Senegal, founded by its leader, Cheikh Ahmadou Bamba (1853-1927). This leader wrote, in Arabic, a large volume of religious poems worshiping Allah, called khassidas – a pre-Islamic genre of oral poetry –, which words are chanted mainly in groups (kurel). In the face of the contemporaneous migrant context of the Senegalese around the world, established specially on this decade in Brazil, and mainly in the Rio Grande do Sul state and, in particular, in the city of Caxias do Sul, these religious practices are being highlighted at the diaspora sphere. Starting with this scenario, the present study aims to research the poetic vocal of these religious chants with Paul Zumthor (1997; 2007) theories that brings the importance of text interpretation beyond obsolete dichotomies, proposing that one could transpose the informative dimension of the discourse, giving relevance to the values, to the pleasure that transcends what is written. On this sense, this thesis has as objective to interpret the relations of the written text, reading, vocality and performance of the mourid religious chants and songs. For that, it shows a historical, social and economic contextualization, taking in account that the Senegalese are transmigrants, establishing connections with the departure and arrival destinations, being the religion one of their ways to express this connection. The ethnography with the mourid community showed the importance of the religious practices for their practitioners, with the khassidas as a tool to keep their faith, a phenomena that was best understood after a trip to Senegal, where it was possible to experience, among other aspects, the care that they display with the original religious texts, as well as their massive dissemination through printed means, and their consumption through digital ways. The khassidas, when chanted on the religious practices, show the power of the vocal poetic and the performance, revealing its sacred value. The kurel khassida has its only and single vocal aesthetic, with special timbre flexibility, a marked Sufi´s influence of connection with the divine. Beyond the vocality, these poems involve elements like the body and the scenario, revealing the performance, that at the diaspora situation, have the role of Touba, Senegal´s sacred city, connection and proximity, making it possible to sustain the mourid identity. With this perspective, the khassidas show themselves as the verbalization of the divine, updating the sonic Baraka (blessing) to the mourids, and the perpetude that goes beyond the text, without abandoning it.
O cenário das religiões no mundo revela-se complexo e singular devido às diferentes formas como são expressas suas práticas. Existem maneiras diversificadas de pertencimento religioso, inclusive em religiões monoteístas tradicionais como o Islã. É o caso do Muridismo, uma confraria Sufi originada no Senegal, fundada pelo líder Cheikh Ahmadou Bamba (1853-1927). Esse líder escreveu, em árabe, grande volume de poemas religiosos de louvor a Allah, denominados khassidas – gênero pré-islâmico de poesia oral –, cujas letras são entoadas principalmente em grupo (kurel). Diante do contexto migratório contemporâneo dos senegaleses pelo mundo – marcado especialmente nesta década para o Brasil, principalmente para o Rio Grande do Sul e para Caxias do Sul, em particular –, essas práticas religiosas ganham destaque na esfera da diáspora. Partindo desse quadro, este estudo investiga a poética vocal desses cantos religiosos por meio das teorias de Paul Zumthor (1997; 2007), que sugere a interpretação do texto além de dicotomias obsoletas, propondo que se ultrapasse a ordem informativa do discurso, dando-se relevância a valores, ao prazer que transcende o que está escrito. Nesse sentido, esta tese tem como objetivo interpretar as relações de escrita, leitura, vocalidade e performance nos cantos religiosos murides. O trabalho apresenta uma contextualização histórica, social e econômica sobre a imigração senegalesa, levando-se em conta que o senegalês é um transmigrante, mantendo conexões com o território de partida e de chegada, sendo a religião uma das formas de expressão dessa ligação. O percurso etnográfico com a comunidade muride revelou a importância dos preceitos religiosos para seus praticantes, tendo nas khassidas uma ferramenta de manutenção de suas crenças, fenômeno que foi melhor compreendido após uma viagem ao Senegal, onde foi possível acompanhar, entre outros aspectos, a ligação dos murides com a religião desde a infância, o zelo que eles apresentam com os originais dos poemas religiosos, bem como sua disseminação massiva por meio das publicações impressas e do consumo dos poemas cantados por meio digitais. As khassidas, quando cantadas nas manifestações religiosas, demonstram o poder da poética vocal e da performance, evidenciando sua sacralidade. O kurel khassida possui uma estética vocal única, com especial flexibilidade timbral, uma marca da influência Sufi de ligação ao divino. Além da vocalidade, esses poemas envolvem elementos como o corpo e o cenário, reveladores de performance que, em situação de diáspora, possuem o papel de proximidade com Touba, a cidade sagrada no Senegal, possibilitando uma manutenção da identidade muride. Sob essas perspectivas, as khassidas apresentam-se como uma verbalização do divino, atualizando o baraka (benção) sônico aos murides, uma perpetuação que vai além da escrita, sem, no entanto, abandoná-la.
Keywords: Monoteísmo - Senegal; Migração - Senegal; Religião; Música sacra; Monotheism - Senegal (Western Africa); Emigration and immigration - Senegal (Western Africa); Religion; Church music